1983
DOI: 10.1002/1097-0142(19831115)52:10<1966::aid-cncr2820521032>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Malignant chondroid syringoma. Report of a case with widespread metastasis and review of pertinent literature

Abstract: The authors report the autopsy case of a 73‐year‐old man with widespread, metastatic, malignant chondroid syringoma, with a long clinical history. Three years after resection of the primary tumor on the back, the tumor recurred at the same site, metastasized to the cervical lymph nodes 7 years later, and finally, after 13 years exhibited widespread metastases. Histologically, the tumor showed cords and nests of cuboidal or polygonal tumor cells with little cellular pleomorphism and few mitoses surrounded by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…Only supportive therapy was continued. 7 In our case, the primary tumor recurred after resection and metastasized during a long clinical course. Liver and kidney metastases were discovered 14 and 15 years after removal of the primary tumor, respectively.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Only supportive therapy was continued. 7 In our case, the primary tumor recurred after resection and metastasized during a long clinical course. Liver and kidney metastases were discovered 14 and 15 years after removal of the primary tumor, respectively.…”
Section: Discussionmentioning
confidence: 59%
“…Bone and widespread metastases are less common. 7,17,22 Involvement of the spinal column is extremely rare. Ishimura et al reported a case of a 73-year-old man who died of complications associated with compression of the upper thoracic spinal cord, 13 years after the initial diagnosis of malignant chondroid syringoma in his back.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…143,[291][292][293][294][295][296][297][298][299][300][301][302] Carcinosarcoma has been reported to arise in a patient with multiple cylindromas. 303 …”
Section: Introductionmentioning
confidence: 99%